Primer of public relations research - Stacks, Don W., ....- (New York (N.Y.) : Guilford press, 2011)
This practical, comprehensive work is widely regarded as the standard course text and practitioner reference on public relations research. Don W. Stacks explains the key role of research in all aspects of contemporary PR practice, from planning a program or campaign to making strategic changes and measuring outcomes. Step-by-step guidelines and tools are provided for using a wide range of qualitative and quantitative methods to accomplish essential research objectives. The book clearly explains technical aspects of data collection and analysis for readers new to measurement and statistics. Every chapter features review questions and a detailed practice problem. A test bank, suggested readings, case studies, and PowerPoint slides are available to instructors using the book in their courses; see the preface for details.
Includes bibliographical references and index.
Keywords: Public relations -- Onderzoek